Uniformity and Difference of Ageing - GRGAS, Stipe (Anafora, 2023)
The author proposes that ageing and old age can be seen as a universal process but also as something that can be differentiated both by time and place. In the central part of the article, the author contends that one way of approaching the topic, particularly if it is addressed as part of the United States polity, is through the lens of American Studies and, more specifically, through the work of R.W.B. Lewis and his idea of the American Adam. It is precisely the self-image of the United States as a country of youth that elides the significance of ageing from the disciplinary agenda. In addition, the author contends that the American socio-economic order marginalizes ageing as incompatible with its dynamics. In the onclusion, the author up dates the issue and shows how today’s pension schemes affect what as precisely designated as a time of retirement.